Electronic Money Determinations in Aceh Besar District - Nanda RAHMI; ALIASUDDIN; NASHRILLAH (Communications of International Proceedings, 2021)
The objective of this study is to examine socioeconomic factors that determine the choice of electronic money in Aceh Besar District.  This study uses cross-sectional data of households as respondents with a total of 250 respondents.  The cross-tabulation method is utilized to examine the socioeconomic factors that determine the choice of electronic money in Aceh Besar District.  The choice is analyzed between males and females to explore the different effects of gender.  The results show that males prefer electronic money compared to females in bank account ownership, ATM card, side job, educational level, poverty level, and family size. Only permanent working status, female prefer electronic money while the male does not. It is necessary to increase the dissemination of electronic money to women because the female population is more than males. Business actors are also more female than male, small and medium enterprises.
Keywords: Electronic Money; Socioeconomic Factor; Gender; Aceh Besar.